2017
DOI: 10.1002/app.45503
|View full text |Cite
|
Sign up to set email alerts
|

A probe into the status quo of interfacial adhesion in the compatibilized ternary blends with core/shell droplets: Selective versus dictated compatibilization

Abstract: A simple approach was applied to probe into the situation of interfacial adhesion in the compatibilized ternary polymer blends with core/shell morphology. The performance of compatibilization was discussed in terms of thermal, rheological, and mechanical properties analyses for blends prepared through different mixing strategies for which maleic anhydride‐grafted high‐density polyethylene (HDPE‐g‐MAH) could be localized at the interface of HDPE/poly(ethylene‐co‐vinyl alcohol) copolymer (EVOH) or HDPE/polyamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Quantification of interfacial adhesion has been carried out based on assessment of mechanical properties; but analyses could not principally provide a close view of events taking place in the vicinity of interface . It was also demonstrated that mixing strategy to a large extent determines interfacial adhesion promotion in the compatibilized ternary blends based on HDPE, PA‐6, and EVOH . Investigations on rheological, thermal, and mechanical behavior confirmed a facile stress transfer across the matrix/shell/core interface in the assigned system as a result of one‐step compatibilization of ternary blends that helps for selective localization of HDPE‐ g ‐MAH, as reflected theoretically in model parameters obtained for interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of interfacial adhesion has been carried out based on assessment of mechanical properties; but analyses could not principally provide a close view of events taking place in the vicinity of interface . It was also demonstrated that mixing strategy to a large extent determines interfacial adhesion promotion in the compatibilized ternary blends based on HDPE, PA‐6, and EVOH . Investigations on rheological, thermal, and mechanical behavior confirmed a facile stress transfer across the matrix/shell/core interface in the assigned system as a result of one‐step compatibilization of ternary blends that helps for selective localization of HDPE‐ g ‐MAH, as reflected theoretically in model parameters obtained for interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic deformation behavior of polymer melts is known to be a powerful tool to predict processability of materials in different manufacturing processes. In addition, the rheological properties are also very sensitive to changes in blend morphology and interaction between the polymer matrix and the dispersed phase [ 4 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to limited compatibility leading to inhomogeneous structures directly influencing the physical properties and therefore the overall performance of the material, the successful generation of combined-property polymers is not easily achieved without drawbacks [ 2 ]. Phase separation behavior is greatly influenced by interfacial tension between the polymers, their density and viscosity ratios [ 3 , 4 ]. To overcome that problem, different compatibilizing systems have been extensively studied over the last years; either motivated by the idea of generating entirely new materials [ 5 , 6 , 7 ] or the improvement of recyclability of mixed polymer waste [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties of ternary blends were the subject of several publications[36,39–43]. Figure 3 shows the results of dynamic thermal‐mechanical properties of neat PP and samples C 1 ‐C 4 .…”
Section: Resultsmentioning
confidence: 99%